Expressividade do corpo: a experiência de vergonha nas academias de ginástica - Barros, Lais Vitória Pinto (2025)
Introduction: This study deals with the experience of shame in fitness centres. It emphasises the body as a central element, so that in their social relations, subjects affect each other while also being affected. When dealing with the theme of the experience of shame within the context of gyms, it is possible to see a common factor between the two, which is the centrality in question, the human body, present in the experience as well as in the occupation of a space. In this sense, every day human life is placed in an environment in which the other and the way the world around them is lived becomes a mechanism that forges identity and influences human relationships. The study emphasises the importance of understanding the body as a phenomenon and suggests the need to re-examine shame in gyms, aiming for new perspectives in understanding social interactions related to the body. Aim: This study aims to analyse the relationship between body expressiveness and the experience of shame in gyms. Methods: This research is a socio-cultural study on the experience of shame and will be qualitative in nature, of the field research type with a focus on the phenomenological approach. The subjects of this research are 8 gym-goers aged between 13-17, considering the adolescent phase, of both sexes. The choice of subjects will be intentional and non-probabilistic. The presence of gender and identity variants will not affect the choice of subjects. Conclusion: The experience of shame, in this sense, leads us to reflect on the need for more welcoming gym environments that integrate the practice of physical activity in a humanised way, attentively welcoming the particularities of the subjects, especially adolescents who are in the process of constructing their identities and are building their references to recognise themselves in themselves.